Diagnostic Accuracy of Stool Tests for Colorectal Cancer Surveillance in Hodgkin Lymphoma Survivors - Ykema, Berbel (J Clin Med, 2020)
Background: Hodgkin lymphoma (HL) survivors have an increased colorectal cancer (CRC) risk. Diagnostic accuracy of quantitative fecal immunochemical testing (FIT, OC Sensor) and/or a multi-target stool DNA test (mt-sDNA, Cologuard(®)) for advanced neoplasia (AN) was evaluated. Methods: 101 HL survivors underwent a surveillance colonoscopy and were asked to perform two stool tests (FIT and mt-sDNA). Advanced adenoma (AA), advanced serrated lesion (ASL), and AN (AA, ASL, CRC) were evaluated. Sensitivity, specificity, and area under the curve (AUC) for AN were calculated for different FIT cut-offs and mt-sDNA with colonoscopy as reference. Results: FIT and mt-sDNA were analyzed in 73 (72%) and 82 (81%) participants, respectively. AN was detected in 19 (26%) and 22 (27%), respectively. AN sensitivities for FIT cut-off of 10 ug Hb/g feces (FIT10) and mt-sDNA were 37% (95% confidence interval (CI): 16–62) and 68% (95% CI: 45–86), with corresponding specificities of 91% (95% CI: 80–97) and 70% (95% CI: 57–86), respectively. AUC for FIT was 0.68 (95% CI: 0.54–0.82) and for mt-sDNA 0.76 (95% CI: 0.63–0.89). Conclusions: In HL survivors, mt-sDNA showed highest sensitivity but with relatively low specificity for AN. Cost-effectiveness analyses is necessary to determine the optimal surveillance strategy.